Tanggung Jawab PT New Era Rubberindo Yang Dinyatakan Pailit Terhadap Hak Pekerja - Anisa Putri Wardani; Nadia Hera Aurelia; Sumriyah Sumriyah (Hakim, 2024)
In the employment relationship there is a work agreement that aims to protect the rights of workers and contains provisions relating to the employment relationship. The existence of Law No. 13 of 2003 concerning Manpower which regulates and protects the rights of workers and provides guarantees for labor. This protection is given so that a company continues to fulfill its obligations to the rights of workers even though the company has been declared bankrupt. PT New Era Rubberindo which was declared bankrupt by the Gresik District Court, where bankruptcy was regulated in Article 2 of Athyat (1) Law No. 37 of 2004 concerning Delaying Debt Payment Obligations In this case PT New Era Rubberindo has met the requirements to be declared bankrupt. Limited Liability Companies that have assets will be detained since the issuance of a court decision and a limited liability company will lose their rights over all the assets they have. The confiscation carried out is a form of accountability of a limited liability company that cannot fulfill the rights of workers and has been declared bankrupt by the District Court. In this accountability Limited Liability Company loses the rights to the assets they have. This study uses a normative juridical method that will discuss the responsibilities of PT New Era Rubberindo which is declared bankrupt to the rights of workers.